Climate Change and Managed Ecosystems - Bhatti, Jagtar (CRC Press, 2009)
Featuring contributions from leading experts in the field, Climate Change and Managed Ecosystems examines the effects of global climate change on intensively constructed or reconstructed ecosystems, focusing on land use changes in relation to forestry, agriculture, and wetlands including peatlands. The book begins by discussing the fragility of ecosystems in the face of changing climates, particularly through human caused increases in atmospheric GHGs. The chapters delineate how and why the climate has changed and what can be expected to occur in the foreseeable future. They identify the potential adaptation responses to reduce the impacts of a changing climate.